PERBANDINGAN EFEK GASTROPROTEKTIF MADU TRIGONA DAN MADU SIDR DIKOMBINASIKAN DENGAN MINYAK JINTAN HITAM (NIGELLA SATIVA) PADA TIKUS WISTAR (RATTUS NORVEGICUS) YANG DIINDUKSI PARASETAMOL - RIRIN WIDIAWATI; DES SURYANI (LP2MTBM MAKARIOZ, 2023)
Paracetamol (Acetaminophen) is the most commonly used analgesic-antipyretic drug worldwide. The risk of abuse and the use of excessive doses can result in damage to the stomach organs (gastric ulcers). Various studies state that black cumin oil and honey are used as medicine for various health problems. Including having a protective effect against damage to the kidneys and liver, but there have been no studies studying the protective effect on the stomach. To compare the effectiveness of the combination of black cumin oil and trigona honey with black cumin oil plus sidr honey on the gastroprotective effect in Wistar rats induced by paracetamol. Experimental research with posttest only with controlled group design. A total of 4 groups were treated for 28 days. Macroskopic examination of the degree of gastric ulcer and histopathological assessment of the number of ulcer scores were carried out. Data analysis used the Kruskal-Wallis test followed by the Mann-Whitney test. There is an effect of giving a single dose of paracetamol 2 g/kg BW on the formation of gastric ulcers in rats characterized by an increase in the degree of gastric ulcers and an increase in the number of ulcer scores on KP (positive control). On macroscopic examination there was no significant difference in the administration of black cumin oil at a dose of 2 ml/kg BW plus sidr honey with a dose of 1 g/kg BW and black cumin oil at a dose of 2 ml/kg BW plus trigona honey at a dose of 7.4 ml/kg BW for 28 days on the stomachs of rats treated with has been induced by paracetamol. Giving paracetamol affects gastric damage in rats. And giving black cumin oil plus honey compared to black cumin oil plus trigona honey had the same gastroprotective effect.